Rapid and Effective Electrical Conductivity Improvement of the Ag NW-Based Conductor by Using the Laser-Induced Nano-Welding Process - Phillip Lee; Jinhyeong Kwon; Jinhwan Lee; Habeom Lee; Young D. Suh; Sukjoon Hong; Junyeob Yeo (Micromachines, 2017)
To date, the silver nanowire-based conductor has been widely used for flexible/stretchable electronics due to its several advantages. The optical nanowire annealing process has also received interest as an alternative annealing process to the Ag nanowire (NW)-based conductor. In this study, we present an analytical investigation on the phenomena of the Ag NWs’ junction and welding properties under laser exposure. The two different laser-induced welding processes (nanosecond (ns) pulse laser-induced nano-welding (LINW) and continuous wave (cw) scanning LINW) are applied to the Ag NW percolation networks. The Ag NWs are selectively melted and merged at the junction of Ag NWs under very short laser exposure; these results are confirmed by scanning electron microscope (SEM), focused-ion beam (FIB), electrical measurement, and finite difference time domain (FDTD) simulation.